Smoking and Depression among Rural Adolescents - Huq, Ehsanul; Afrin, Sharmina; Rahman, Salequr; Zinia, Sumsun Nahar; Mostofa, Sharmin (Delta Medical College Journal, 2025)
Background: One factor that influences smoking in adolescents is depression. Cross-sectional research has found significant co-morbidity between depression and cigarette smoking in adolescents. Objectives: To find out the factors related to smoking and depression among adolescents in the selected villages of Savar Upazilla of Bangladesh. Materials and method: This descriptive type of cross sectional study was carried out with the objective to assess the factors related to smoking and depression among adolescents in a rural community of Bangladesh. Total 270 respondents were selected from the village by non-probability convenience sampling technic and data were collected by face to face interview with the help of semi structured pre-tested questionnaire. The 6-ITEM Kutcher Adolescent Depression (KADS-6) Scale was used to measure the presence of depression. Results: Out of 270 respondents, 55.18% lived in nuclear family and majority (52.96%) of the respondents was smoker and started smoking around the age of 14.5 years. Peer smoking and parent smoking play an important role to start smoking among the adolescents. In this study 69.23% of the respondents were influenced about smoking by their friends. Conclusion: More than half of the adolescents had already started smoking. Tobacco use is an unhealthy behavior that remains remarkably resistant to modification. This study is very important in the point of public health. Delta Med Col J. Jan 2022;10(1): 20-24